Digital Transformation of Islamic Education Learning: A Study of iPad-Based Innovation in Enhancing Student Learning Engagement - Hendi Kariyanto; Siti Hanipah; Muhammad Dimas; Revaldo Xsanal Hakim; Rangga Saputra (Dirasah International Journal of Islamic Studies, 2025)
Digital transformation has become a fundamental imperative in modern educational systems, including within the context of Islamic Religious Education (IRE). While mobile learning technologies offer significant potential for enhancing student engagement, their implementation in religious education still faces challenges related to digital literacy, infrastructure limitations, and alignment with Islamic values. This study aims to investigate the role of iPad-based learning innovation in enhancing student engagement in IRE within the framework of digital transformation. Employing a qualitative research approach with a case study design, this research was conducted at an Islamic primary school implementing a one-to-one iPad program. Data were collected through Classroom observations, semi-structured interviews, and document analysis involving teachers, students, and school administrators. The findings reveal that iPad integration significantly transforms instructional practices by promoting interactive, student-centered, and technology-enhanced learning environments. The use of multimedia content, digital applications, and online assessments increases students' behavioral, emotional, and cognitive engagement. Analysis using the SAMR model indicates that iPad integration extends beyond basic substitution, reaching modification and redefinition levels that enable innovative learning experiences. The implications of this research suggest that the effectiveness of iPad-based learning depends on alignment among technology, pedagogy, and institutional support, requiring sustained investment in infrastructure and teacher professional development to ensure a successful digital transformation in Islamic education.